2020
DOI: 10.1186/s12301-020-00082-1
|View full text |Cite
|
Sign up to set email alerts
|

Scrotal leiomyoma: a rare cause of scrotal swelling

Abstract: Background Leiomyomas are benign smooth muscle tumours predominantly found in the uterus. Rarely, they may be located in the ovaries, scrotum, bladder, lungs, vascular structures and spermatic cord. Case presentation We managed a 39-year-old man who presented with a year history of progressive right-sided hemiscrotal swelling. The right scrotal mass was excised, and histology showed scrotal leiomyoma. Conclusion Scrotal leiomyoma is very rare and challenging to diagnose pre-operatively as a cause of scrotal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Imaging studies revealed a left paratesticular mass, and surgery confirmed the histopathological features consistent with scrotal leiomyoma [12]. Egharevba et al ( 2020) also presented a case of scrotal leiomyoma in a 39-year-old male with a progressive right-sided hemiscrotal swelling over one year, which was excised, and histopathology revealed scrotal leiomyoma [13]. Table 1 summarizes the previously reported cases of scrotal leiomyoma.…”
Section: Discussionmentioning
confidence: 91%
“…Imaging studies revealed a left paratesticular mass, and surgery confirmed the histopathological features consistent with scrotal leiomyoma [12]. Egharevba et al ( 2020) also presented a case of scrotal leiomyoma in a 39-year-old male with a progressive right-sided hemiscrotal swelling over one year, which was excised, and histopathology revealed scrotal leiomyoma [13]. Table 1 summarizes the previously reported cases of scrotal leiomyoma.…”
Section: Discussionmentioning
confidence: 91%
“…The primary treatment is surgical excision of the local lesion [20]. Complete surgical resection of the tumor is curative and recurrence after adequate resection is rare.…”
Section: Scrotal Leiomyomamentioning
confidence: 99%